Diffusion of Scale Effects between European Regions - Jürgen Antony (Universität Augsburg, Institut für Volkswirtschaftslehre, 2005)
This paper develops a multi regional growth model of the second generation type with horizontal and vertical innovations. Technology goods are tradable between regions, creating a regional analogy of the weak scale effect introduced by Jones (2004). Per capita production in one region is a function of the weighted population sizes of trading partner regions. Thus the scale of partner regions diffuses between them. This result is empirically tested using data on the NUTS regions of the EU 15. A highly significant relationship is found between per capita GDP and an interregional scale variable, defined as a weighted sum of the populations of all EU 15 regions.
urn:nbn:de:bvb:384-opus4-347273
Keywords: R12; O52; O33; 330; Regional growth; scale effects; interregional trade